The Kuhn-Tucker's theorem for inequalities in infinite dimension - Ferreira, M. A. M. (2012)
It is intended, in this work, to present the Kuhn-Tucker theorem with the consideration of infinite inequalities. So the mathematical fundaments of this result, not so important in Mathematical Programming but a very challenging problem from the mathematical point of view, are presented in a very simple way. It is shown how this result can be obtained in the context of real Hilbert spaces using the separation theorems.